(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines modern aspects of the use of mathematical models in solving problems of sustainable development of enterprises. The essence of the concept of sustainable development was considered and its importance for enterprises in the modern dynamic business environment was determined. The role of mathematical modeling in the decision-making process based on the application of specific methods and tools that help to analyze and optimize the production processes of economic entities in the context of sustainable development is studied. A complex of specialized mathematical models used for modeling sustainable development is considered, including such aspects as linear and non-linear programming, simulation theory, game theory, differential equations, etc. The peculiarities of the application of these models in the activities of enterprises were analyzed and their effectiveness in ensuring the achievement of sustainable development was determined. Practical examples of the implementation of economic and mathematical models at enterprises of various industries on the basis of reducing resource consumption, optimizing production processes, waste and risk management strategies, as well as planning future investments in sustainable development were studied. The importance of the development and improvement of economic-mathematical modeling methods for achieving the goals of sustainable development of economic entities is determined. The essence of challenges and obstacles that arise in the process of implementing economic and mathematical models to achieve sustainable development of enterprises, which include the objective need for access to a large amount of data, the complexity of interaction with counterparties, as well as the instability of the modern economic environment, is considered. Strategies and recommendations for overcoming these challenges are proposed, including the development of information systems and the actualization of the needs of business entities regarding the importance of sustainable development. The necessity of integrating mathematical models in the planning and economic activities of enterprises to achieve the efficiency of their sustainable development is determined. The importance of applying economic-mathematical modeling to increase the efficiency of enterprises and stimulate their sustainable activity to achieve strategic goals is proven.